A mass spectrometry method for the determination of the species of origin of gelatine in foods and pharmaceutical products. (1st January 2016) - Grundy, H.H.; Reece, P.; Buckley, M.; Solazzo, C.M.; Dowle, A.A.; Ashford, D.; Charlton, A.J.; Wadsley, M.K.; Collins, M.J.
Highlights: We report results comparing methods to determine the species origin of gelatine. An LC–MS/MS method to support food authenticity testing is presented. We screen for bovine, porcine and avian marker peptides from gelatine and collagen. The method can be adapted to accommodate many other species including horse. PCR and ELISA methods were also evaluated. Abstract: Gelatine is a component of a wide range of foods. It is manufactured as a by-product of the meat industry from bone and hide, mainly from bovine and porcine sources. Accurate food labelling enables consumers to make informed decisions about the food they buy. Since labelling currently relies heavily on due diligence involving a paper trail, there could be benefits in developing a reliable test method for the consumer industries in terms of the species origin of gelatine. We present a method to determine the species origin of gelatines by peptide mass spectrometry methods. An evaluative comparison is also made with ELISA and PCR technologies. Commercial gelatines were found to contain undeclared species. Furthermore, undeclared bovine peptides were observed in commercial injection matrices. This analytical method could therefore support the food industry in terms of determining the species authenticity of gelatine in foods.